Políticas públicas e estratégias para interação universidade-empresa e transferência de tecnologia - Dellaqua, Silmara Maria (2020)
When considering that universities and companies represent an important innovation axis for the country’s socioeconomic development, especially when it comes to creating valuable knowledge, government public policies have increasingly structured and encouraged university-company interactions for the transfer of technology. Applied to the Brazilian scenario, the objective of this study is to identify public policies for C, T & I, activities, government programs and potential actions in favor of technology transfer in federal universities in the university-company context. The problematic part of the question is that, if, on the one hand, government support aims to structure and financially subsidize universities, and other scientific and technological institutions, for C, T & I through research and development of innovation and technology, on the other it is up to the university to undertake actions só that this public effort reaches the productive sector, either through innovative academic entrepreneurship or through university-business cooperation. In both cases, the desired objective is the transfer of technological knowledge and technology. Thus, this research uses an integrative systematic literature review and documentary research to answer the question: how does government support favor the transfer of technology in federal universities? First, a systematic integrative literature review is carried out to highlight the main conflicting points in the government- university-productive sector interaction, presenting the alternatives adopted in the European, American, Latin and Brazilian contexts for the issues raised. In the chapter dedicated to the presentation and analysis of results, data from documentary research are then presented, with emphasis on two universities selected for exploration on how they undertake actions to transfer technology. The federal universities that empirically illustrate this research were selected from among the most active, both in terms of volume of deposits and financial value moved from their technology transfer actions. It is believed that in this way processes with maturity for discussion can be identified in the light of the theoretical framework. For the analysis of the results, it was sought through content analysis to establish a discussion between the elements of the research. The conclusions of this work suggest that the government has a support structure for SNCTI operators, including federal universities, which promotes financial and non- financial investments through funding agencies and directly by subsidizing higher education activities. The research revealed the actions of the universities analyzed, bringing the productive- business sector closer to establish partnerships and share knowledge in cooperation in technological projects. Finally, it is suggested by the need for future research to strengthen this important innovation axis for the country.